TRANSDISCIPLINARITY AS THE ASPECT OF EDUCATION OF INFORMATIONAL SOCIETY (PHILOSOPHICAL ANALYSIS) - Кошетар, У. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The article is devoted to the philosophical analysis of the essential features of transdisciplinarity as an important component of the modern education of the information society. The civilization process as a determinant of transformational tendencies and the philosophical concept in contemporary educational policy are considered. The necessity of considering the idea of tra-nsdisciplinarity within the limits of philosophical discourse has been updated.